Comparison of metallothionein induction in response to cadmium in the gills of the bivalve molluscs Mytilus galloprovincialis and Ruditapes decussatus - Bebianno, Maria João (2020)
Metal binding characteristics and metallothionein induction differ markedly among the gills of the bivalve molluscs Mytilus galloprovincialis and Ruditapes decussatus exposed to sublethal cadmium concentrations (100 μg/l). The rates of cadmium uptake as well as the percentage of cadmium bound to the cytosol were significantly higher in the gills of M. galloprovincialis when compared with that of R. decussatus. Similarly metallothionein concentration detected in the gills of M. galloprovincialis increase fourfold while for the clam R. decussatus metallothionein concentrations increased only twofold.